2015
DOI: 10.1002/bab.1374
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced power generation in annular single‐chamber microbial fuel cell via optimization of electrode spacing using chocolate industry wastewater

Abstract: Development and practical application of microbial fuel cell (MFC) is restricted because of the limitations such as low power output. To overcome low power limitation, the optimization of specific parameters including electrode materials and surface area, electrode spacing, and MFC's cell shape was investigated. To the best of our knowledge, no investigation has been reported in the literature to implement an annular single-chamber microbial fuel cell (ASCMFC) using chocolate industry wastewater. ASCMFC was fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 36 publications
0
9
0
3
Order By: Relevance
“…An air‐cathode ASCMFC in cylindrical shape was fabricated and assembled as reported in our previous study (Fig. ) . An approximately 91 mm diameter coaxial cylinder was created with 71 mm diameter inner cylinder and 30 mm length.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…An air‐cathode ASCMFC in cylindrical shape was fabricated and assembled as reported in our previous study (Fig. ) . An approximately 91 mm diameter coaxial cylinder was created with 71 mm diameter inner cylinder and 30 mm length.…”
Section: Methodsmentioning
confidence: 99%
“…A 3.5 cm (height) × 11 cm (length) 30 wt% wet proofed carbon cloth (Type A, E‐TEK, Somerset, NJ, USA), with 0.5 mg/cm 2 of Pt on the liquid‐facing side, was placed in the inner cylinder as the cathode electrode . The design was modified by fixing electrode spacing at 0.7 cm and the optimized ASCMFC was acquired by considering our previous work . The system was monitored using a data acquisition system at an interval of 15 min to record the voltage outputs of the ASCMFC.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some researchers studied the principles of MFC especially in selecting microorganisms of interest [11], economical substrate [12], pilot-plant study for power production [13], modeling of biofilm constitution with engineering aspect [14], and role of electron acceptors in MFCs [30], respectively. The other groups verified the importance of this technology for power production [15][16][17][18][19][20][21]. Several kinds of mediators had applied in such system to augment the electron transfer rate, but they are generally expensive to be used in pilot or industrial scale program of MFC manufacture and showed toxicity to secreted biocatalysts for longperiod operation [22].…”
Section: Introductionmentioning
confidence: 99%